Chemical and Mineralogical Characterisation of Clayey Sands from the Ivorian Sedimentary Basin in Road Construction - Kouassi, Kouakou Pierre; Atto Yapi, Désiré Sosthène Ronald; Konin, Athanase; Grehoa, Abalé Martial (European Scientific Journal, ESJ, 2023)
In Ivory Coast, particularly in the south, most paved and unpaved roads are made of clayey sand, given its availability. The early degradation of roads is related to a strong sensitivity of certain materials to the environment (climate, geology, and degrees of alteration) and a poor knowledge of the geotechnical properties could slow down their use in road construction. Within this framework, this paper focuses on determining the chemico-mineralogical nature of the clayey sands of the localities of Bingerville and Samo, in the South-East of Ivory Coast. Tests were conducted based on the chemical and mineralogical analyses. Chemical elements were determined by atomic absorption spectrometry, colorimetry, complexometry, and gravimetry. Organic matter was determined using the Rock-Eval 6 pyrolysis method, while the mineralogical composition was determined using a Bruker D8 ADVANCE diffractometer. The chemico-mineralogical analyses reveal that the clayey sands from Bingerville and Samo are more enriched in silica oxide (SiO2) but less enriched in iron oxide (Fe2O3). All the soils studied have a degree of laterization greater than 2, which suggests that they are non-lateritic soils. The low Total Organic Carbon (TOC) values lies between 0.1 and 0.15% by weight, which reflects the extremely low amount of organic matter in these soils. This indicates the possibility of treating these soils with hydraulic binders. The mineralogy of the studied soils denotes that they are composed of kaolinite and illite.